The elusive yeast interactome - Goll, Johannes (BioMed Central, 2006)
Simple eukaryotic cells such as yeast could contain around 800 protein complexes, as two new comprehensive studies show. But slightly different approaches resulted in surprising differences between the two datasets, showing that more work is required to get a complete picture of the yeast interactome.